Review of advanced research on swine Actinobacillus pleuropneumoniae vaccine development strategy - Tesfaye, Adehanom Baraki; Han, Rui; Tao, Zhengyu; You, Liuchao; Zhu, Jiayao; Gao, Pengcheng; Fu, Lei; Chu, Yuefeng (Frontiers in Immunology, 2025)
Actinobacillus pleuropneumoniae (App) infection is a major respiratory disease that causes severe economic losses. It is highly infectious and exhibits multiple serotypes, which complicates prevention and control. This review discusses the new-generation vaccine development strategies and the role of virulence factors—such as App toxins, capsular polysaccharide (CPS), lipopolysaccharide (LPS), and outer membrane proteins (OMPs)—in vaccine design. Traditional vaccines offer limited cross-protection, whereas live attenuated vaccines, subunit vaccines, and toxin-based vaccines show promising improvements in efficacy and safety. Current and near-generation subunit and toxin vaccines mainly focus on conserved antigens, incorporating App toxins, OMPs ApfA, and GALT, which significantly enhance cross-protection and safety. Other approaches, including DNA vaccines and combined multivalent vaccines targeting highly prevalent App serotypes and integrating antigens from other pathogens, represent a modern strategy aimed at enhancing cross-serotype protection, minimizing side effects, and enabling differentiating infected from vaccinated animal (DIVA) capability.